Hyperidentities with permutations in invertible binary algebras - Shahnazaryan, Davit; Davidov, Sergey (Armenian Journal of Mathematics, 2020)
In this paper, using hyperidentities with permutations we obtained characterization invertible algebras of various types of linearity.
Keywords: Invertible algebra; Second-order formula; Hyperidentity with permutations; Isotopy